SURVEILLANCE CYBER-PHYSICAL SYSTEM AS A PART OF INTERNET OF VEHICLES (Computer systems and information technologies, 2024)
Integration of cyber-physical surveillance systems (CPSS) into the Internet of Vehicles (IoV) paradigm represents a transformative approach to enhancing transportation safety and efficiency. This article discusses the design, implementation, and application of CPSS as part of IoV ecosystems. Leveraging advancements in sensor technologies, communication protocols, and data analytics, CPSS within IoV enables real-time monitoring, analysis, and response to road conditions, incidents, and emergencies. Our research explores the architecture and functional capabilities of CPSS, including sensor deployment, data fusion, anomaly detection, and decision support mechanisms. We investigate the synergistic interaction between CPSS and IoV platforms, facilitating seamless data exchange, collaboration, and compatibility between automotive and infrastructural domains. Additionally, we discuss potential applications of CPSS in traffic management, law enforcement, emergency response, and urban planning, emphasizing its role in enhancing transportation safety, optimizing resource allocation, and preventing congestion and accidents. Through empirical evaluations and thematic studies, we demonstrate the effectiveness, scalability, and societal impact of integrating CPSS into IoV ecosystems. This research contributes to the development of intelligent transportation systems and underscores the transformative potential of CPSS within the IoV context.
Keywords: cyber-physical system; Internet of Vehicles; intelligent transportation systems; edge computing